Brief report: symmetricity of radiographic and MRI-detected structural joint damage in persons with knee pain – the Joints on Glucosamine (JOG) Study. Issue 8 (August 2015) - Roemer, F.W.; Jarraya, M.; Kwoh, C.K.; Hannon, M.J.; Boudreau, R.M.; Green, S.M.; Jakicic, J.M.; Moore, C.; Guermazi, A.
Summary: Objective: Most MRI-based osteoarthritis (OA) studies have focused on a single knee per person and thus, data on bilaterality is sparse. Study aim was to describe symmetricity of MRI-detected OA features in a cohort of subjects with knee pain. Design: Participants were 169 subjects with chronic knee pain who had 3 T MRI of both knees using the same protocol as in the Osteoarthritis Initiative. Knees were read for cartilage damage, bone marrow lesions (BMLs), and meniscal damage according to the Whole-Organ Magnetic Resonance Imaging Score (WORMS) system. Chi 2 tests were used to compare the proportion of knees with unilateral tissue pathology to the proportion what would be expected if both knees were independent. We further used percent agreement and linear weighted kappa statistics to describe agreement of cartilage damage and BMLs in the same articular plates. Results: 51.2% of participants were men, mean age was 52.1 (±6.2), mean BMI was 29.0 kg/m 2 (±4.1). All plates showed a significant higher degree of symmetricity for cartilage damage as evidenced by weighted kappas ranging from 0.32 to 0.59. For BMLs the degree of symmetricity was higher for the patella, trochlea, medial tibia, lateral femur, and medial femur; for meniscal damage the degree of unilaterality was lower for all medial meniscal subregions but not all lateral. Kappas ranged between 0.52 and 0.68 for cartilage and 0.30 and 0.55 for BMLs for the four subregions with highest agreement. Conclusion: A higher degree of symmetricity of tissue damage than expected by chance was observed in this cohort of subjects with knee pain.